Persepsi Motivasi Menetap Atau Pindah Masyarakat Terhadap Dampak Perubahan Pemanfaatan Lahan Di Kampung Baterman dan Petempen - Adistianti Syahrani; Sugino Soetomo (Jurusan Perencanaan Wilayah dan Kota, 2019)
Petempen and Baterman villages are one of the villages located in Kembangsari Village, Semarang City. As a village located in the center of the city, this village has been targeted by investors so that it is one of the goals to develop investments in the commercial business sector. The limited land caused the construction of hotels and apartments around the village to take up land in the surrounding villages. The impact of this phenomenon triggered the growth of new economic activities in the neighborhoods of Kampung Petempen and Baterman. Changes in land use that occur leads to the growth of small businesses. Both villages are very vulnerable to the impact of development from the surrounding environment. The purpose of this study was to analyze the motivation of settling or moving people towards the impact of changes in land use around the village. This research includes descriptive research with a quantitative approach. Data collection is done by questionnaires, interviews and observations. The sampling technique is done by random sampling. The results of this study are known that the community's permanent perception of 75% wants to survive, 25% of the community wants to move. Sedentary motivation is influenced by strategic location while the motivation to move is influenced by the inconvenience of staying. The development around the village did not affect the development of other investments (development) in Petempen and Baterman villages. The impact caused leads to the development of small business growth in the location of residential settlements.